An ever closer union . . . of linguistic diversity - Tomozeiu, Daniel (Studies in Second Language Learning and Teaching, 2017)
The analysis carried out between October 2014 and February 2015 by a team of researchers from the University of Westminster with support from colleagues from across the EU identified the linguistic communities across the 28 EU member states as recognized (or not) by the country’s legislation and the linguistic rights of these communities in education, judiciary and public services. The findings present a complex picture of different linguistic traditions, as well as different levels of minority language use. Education and media appear as the two areas where these minority languages are most used. The diversity of national policies across the EU towards minority languages is highlighted. At the same time, a number of factors that influence the use of minority languages in one context and not in another are identified. Finally, a policy approach that would enhance education in minority languages, strengthen community cohesion and diversity in a globalizing world is put forward.